Associations between self‐reported respiratory symptoms and non‐specific psychological distress following exposure to a prolonged landscape fire. (12th September 2021) - Samuel, Riana; Carroll, Matthew T. C.; Ikin, Jillian F.; Gao, Caroline X.; Del Monaco, Anthony; McFarlane, Alexander; Berger, Emily; Maybery, Darryl; Broder, Jonathan; Brown, David; Sim, Malcolm R.; Walker, Judi; et al.
Abstract: We investigated the association between respiratory symptoms and psychological distress in the context of a prolonged smoke event, and evaluated whether smoke exposure, or pre‐existing respiratory and mental health conditions, influenced the association. Three thousand ninety‐six residents of a rural town heavily exposed to smoke from the 6‐week Hazelwood coal mine fire, and 960 residents of a nearby unexposed town, completed Kessler's psychological distress questionnaire (K10) and a modified European Community Respiratory Health Survey. Logistic regression models evaluated associations between distress and respiratory symptoms, with interactions fitted to evaluate effect modification. Smoke exposed participants reported higher levels of distress than those unexposed, and participants reporting respiratory symptoms recorded higher levels of distress than participants without respiratory symptoms, irrespective of exposure. 5‐unit increments in K10 scores were associated with 21%–48% increases in the odds of reporting respiratory symptoms. There were significant interactions with pre‐existing asthma, chronic obstructive pulmonary disease and mental health conditions, but not with smoke exposure. Although participants with pre‐existing conditions were more likely to report respiratory symptoms, increasing distress was most strongly associated with respiratory symptoms among those without pre‐existing conditions. Communities exposed to landscape fire smoke could benefit from interventions to reduce both psychological and respiratory distress.